2021
DOI: 10.1017/s0022215121000803
|View full text |Cite
|
Sign up to set email alerts
|

A policy of day-case sinonasal surgery is safe, well tolerated and cost-effective

Abstract: Objective Practices vary regarding the timing of discharge after sinonasal surgery. This study aimed to examine the cost-effectiveness of same-day discharge compared to next-day discharge after sinonasal surgery. Methods A retrospective single-surgeon audit of sinonasal surgery over a 12-month period was performed. Demographic and clinical details, including distance travelled home, timing of discharge, hospital re-presentation, and complications, were collected and compared between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A single surgeon study of 181 patients (both day-case and overnight stay) from New Zealand concluded that day-case sinonasal surgery was safe and acceptable to patients. 24 An earlier case note review involving 105 day-case ESS patients drew similar conclusions and suggested important factors in successful implementation of day-case ESS were careful patient selection and dedicated day-case infrastructure. 25 A French study focussing on patient reported outcomes for day-case endoscopic ethmoidectomy reported no readmission and no major complications in their series of 74 patients.…”
Section: Discussionmentioning
confidence: 77%
“…A single surgeon study of 181 patients (both day-case and overnight stay) from New Zealand concluded that day-case sinonasal surgery was safe and acceptable to patients. 24 An earlier case note review involving 105 day-case ESS patients drew similar conclusions and suggested important factors in successful implementation of day-case ESS were careful patient selection and dedicated day-case infrastructure. 25 A French study focussing on patient reported outcomes for day-case endoscopic ethmoidectomy reported no readmission and no major complications in their series of 74 patients.…”
Section: Discussionmentioning
confidence: 77%
“…A single surgeon study of 181 patients (both day-case and overnight stay) from New Zealand concluded that day-case sinonasal surgery was safe and acceptable to patients. 14 An earlier case note review involving 105 day-case ESS patients drew similar conclusions and suggested important factors in successful implementation of day-case ESS were careful patient selection and dedicated day-case infrastructure. 15 A French study focussing on patient reported outcomes for endoscopic ethmoidectomy reported no readmission and no major complications in their series of 74 patients.…”
Section: Discussionmentioning
confidence: 77%
“…13 Such provision is substantially less costly that a hospital bed. Day-case surgery can support more cost-effective and resource-efficient provision of surgical services by preventing unnecessary bed occupation 14 and reducing risks of hospital acquired infection and deconditioning. 22 A further consideration that will impact the surgical management of sinonasal disease is the emergence of balloon sinuplasty which can be performed under local anaesthetic, and therefore as a day-case or out-patient office procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There is a drive to increase day-case surgery rates, thereby reducing surgical waiting lists and hospital admissions, and improving service efficiency and patient satisfaction. 1 The article by Edafe et al in this month's issue of The Journal of Laryngology & Otology is therefore timely. 2 The authors sought to determine the same-day discharge rate for functional endoscopic sinus surgery (FESS) in a tertiary rhinology unit and identify factors that resulted in an overnight in-patient stay.…”
Section: Jonathan Fishman and Edward Fisher Editorsmentioning
confidence: 99%
“…There is a drive to increase day-case surgery rates, thereby reducing surgical waiting lists and hospital admissions, and improving service efficiency and patient satisfaction. 1 The article by Edafe et al . in this month's issue of The Journal of Laryngology & Otology is therefore timely.…”
mentioning
confidence: 99%